An evaluation of the genotoxicity and 90‐day repeated‐dose toxicity of a CBD‐rich hemp oil - Clewell, Amy; Glávits, Róbert; Endres, John R.; Murbach, Timothy S.; Báldi, Péter Tamás; Renkecz, Tibor; Hirka, Gábor; Vértesi, Adél; Béres, Erzsébet; Szakonyiné, Ilona Pasics (Journal of applied toxicology, 2023)
Currently, there is much interest in the sales and study of consumable Cannabis sativa L. products that contain relatively high levels of cannabidiol (CBD) and low levels of Δ‐9‐tetrahydrocannabinol. While there are published safety evaluations for extracts containing low concentrations of CBD, toxicological assessments for those with higher concentrations are still scant in the public domain. In this paper, genotoxicity tests and a 90‐day repeated‐dose toxicity study of an ethanolic extract of C. sativa containing ~85% CBD were performed following relevant OECD guidelines. No increased gene mutations were observed in a bacterial reverse mutation assay compared to controls up to the maximum recommended concentration of the guideline. An in vitro chromosomal aberration assay showed no positive findings in the short‐term (3 h) treatment assays. Long‐term treatment (20 h) showed an increased number of cells containing aberrations at the highest dose of 2 μg/mL, which was outside of historical control levels, but not statistically significantly different from the controls. An in vivo micronucleus study showed no genotoxic potential of the test item in mice. A 90‐day repeated‐dose gavage study using 0, 75, 125, and 175 mg/kg bw/day showed several slight findings that were considered likely to be related to an adaptive response to consumption of the extract by the animals but were not considered toxicologically relevant. These included increases in liver and adrenal weights compared to controls. The NOAEL was determined as 175 mg/kg bw/day, the highest dose tested (equivalent to approximately 150 mg/kg bw/day of CBD). A toxicological assessment of an ethanolic Cannabis sativa extract containing ~85% CBD was performed. Genotoxicity concern based on a bacterial reverse mutation assay, an in vitro chromosomal aberration assay, and an in vivo mouse micronucleus assay was considered low. A 90‐day repeated dose study in rats showed some adaptive responses but no toxicological concern. The NOAEL was 175 mg/kg bw/day, the highest dose tested.